2024
DOI: 10.3390/educsci14030316
|View full text |Cite
|
Sign up to set email alerts
|

Game On, Reflection On: Reflection Diaries as a Tool for Promoting Reflection Skills in Geography Lessons

Geraldine Baßeng,
Alexandra Budke

Abstract: In this study, a diary was developed and used by students to reflect on digital games in geography lessons. The students’ reflection results, through the use of the diary, were compared with reflections without instructional guidance. These results show a significant improvement in reflection through the use of the reflection diary compared to a previous study. Through the combination of lessons, play phases, and the reflection diary, a learning arrangement that enables in-depth reflections at different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the article "Game On, Reflection On: Reflection Diaries as a Tool for Promoting Reflection Skills in Geography Lessons", by Baßeng and Budke [10], the researchers explore how reflection diaries could help students develop critical thinking skills in geography lessons that used digital games. The researchers found that the diary itself played a key role: by prompting reflection, it helped students step outside of the mindset of being a player and analyze the game more critically.…”
Section: Section I-articlesmentioning
confidence: 99%
“…In the article "Game On, Reflection On: Reflection Diaries as a Tool for Promoting Reflection Skills in Geography Lessons", by Baßeng and Budke [10], the researchers explore how reflection diaries could help students develop critical thinking skills in geography lessons that used digital games. The researchers found that the diary itself played a key role: by prompting reflection, it helped students step outside of the mindset of being a player and analyze the game more critically.…”
Section: Section I-articlesmentioning
confidence: 99%